A Production systems study on Cutter Exchange Manufacturing Corporation - Duque, Sonia Teresa C.; Zomil, Joanna (Diliman, Quezon City College of Engineering, 1996)
Cutter Exchange Manufacturing Corporation is a garment from which has blouses and dresses for women and t-shirts for men as its product. Through the analyses of it system, the problem areas carefully studied were no documentation of its production capacity, no production planning and inefficient process flow. To remedy these problems, the group determined its production capacity by using aggregate capacity planning techniques. Ti improve its process, it was recommended to change the process from sewing the entire product by one sewer to a sewing each part of the product by one sewer. The time saved by using the proposed process was calculated using CPM.
IE 151
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Cutter Exchange Manufacturing Corporation; Clothing trade; Production engineering